Analysis of Certainty and Fairness of Gender Disparities Towards Victims of Sexual Violence - Nada Ainiyyah Tamy Abdullah; Yuni Priskila Ginting (Publikasi Indonesia, 2026)
Gender is a social (not biological) construct that can cause injustice for both men and women. With the increasing global awareness of sexual violence and human rights (Law No. 39/1999), this study examines the shift in Law No. 12/2022 which provides inclusive protection for all genders. This research aims to analyze gender equality in the context of sexual violence and identify the legal gaps in addressing sexual violence, which historically targeted only women. The study also examines the impact of Law No. 12 of 2022, which extends protection to all genders. This normative juridical research analyzes legal norms and their application in the Sexual Violence Crime Law (TPKS Law), focusing on gender issues, sexual violence, and the shift toward a more inclusive approach. The research shows that gender inequality, particularly in the legal treatment of men as victims of sexual violence, has been addressed with the introduction of Law No. 12 of 2022. This law is more inclusive, offering protection not only to women but to all genders, representing a significant shift toward equality in legal protection for sexual violence victims. The conclusion of this study is that while gender equality is a fundamental principle, there is still a need for consistent legal implementation and deeper understanding of gender equality in the context of sexual violence. The enactment of Law No. 12 of 2022 marks a positive step toward more inclusive legal protection for all genders, although challenges remain in its consistent application.